ENGLISH AND MINANGKABAU SUFFIXES - Syahputri, Diani; Dewi, Ratna Sari; Juliasih, Sofia (IJOSMAS, 2022)
This study purposed to describe the similarities and dissimilarities of Suffixes in English and Minangkabau language. There are some forms, distribution, function and meaning of suffixes in English and Minangkabau. The objective of the study are to describe some similarities and dissimilarities of using suffixes between English and Minangkabau in terms of form, distribution, function, and meaning. Thus it implemented in library research. The source of data referred to English and Minangkabau for vocabulary books. The findings shows that there are some similarities and dissimilarities of suffixes in English and Minangkabau. There are seven suffixes in English, such as ; -en, -ify, -er, ize, -less,-ness, and -al. In Minangkabau , they are -an, and -i. In English and Minangkabau has two forms, namely; vocal phonemes and consonant phonemes. In English has three distribution, namely; nouns, verbs, and adjectives. In Minangkabau has four distribution , namely; noun, verbs, adjective and numeral. In English and Minangkabau has five functions, namely; noun become adjective, noun become verb, adjective become verb, noun become noun and verb become verb. In English has six meanings, namely; the meaning of make or become, made of, to make, to do an action, the person who and tool. In Minangkabau has six meanings , namely; the meaning of tool, something related, command, to make, request and put.